Selection Policy and the Labour Market Outcomes of New Immigrants - Deborah A. Cobb-Clark (Institute for the Study of Labor (IZA), 2004)
Many countries are placing a greater emphasis on productive skills in the immigrant selection policies as a way of achieving national objectives regarding immigration. These changes stem primarily from the belief that skill-based immigrants do better in some sense and provide greater economic benefits than immigrants admitted on the basis of their family relationships. This paper takes advantage of a change in Australian selection policy in the 1990s to assess the extent to which selection policy can facilitate employment outcomes for new arrivals over the medium run. The results indicate that the increased emphasis on productive skills in the selection process led to striking differences in the human capital endowments of new immigrants. These improvements in human capital in turn completely explain the higher participation rates amongst immigrants arriving in Australia at the end of the 1990s. Moreover, approximately half of the fall in men?s unemployment rates also stems from increases in productive skills, though the substantial decline in women?s unemployment rates are driven solely by changes in the returns to skills rather than skill levels themselves. Overall, these results indicate that there is a large potential for selection policy to influence immigrant outcomes not just immediately after migration but also in the medium run. At the same time, it is also clear that income-support policy and the overall state of the Australian labour market also had a hand in improving the labour market position of new arrivals.
Keywords: J22; J61; J20; 330; immigration; selection policy; unemployment; labour market participation; Einwanderungsrecht; Migrationspolitik; Qualifikation; Humankapital; Arbeitslosigkeit; Erwerbstätigkeit; Migranten; Australien